Broadening the Bandwidth of Piezoelectric Energy Harvesters Using Liquid Filled Mass. (2015) - Jackson, Nathan; Stam, Frank; Olszewski, Oskar Z.; Houlihan, Ruth; Mathewson, Alan
Abstract: A narrow bandwidth is one of the most challenging issues that vibrational energy harvesters have to overcome. This paper demonstrates a novel method of broadening the bandwidth without significantly reducing the peak output voltage. The method uses a liquid filled mass to create a sliding mass effect in order to broaden the bandwidth. The fluid mass increased the full-width-half-maximum (FWHM) value from 1.6 Hz to 4.45 Hz with no significant decrease in peak-to-peak voltage when compared to an empty mass. The fluid filled mass has a non-linear mass distribution during low frequency, high acceleration applications.